CFD investigation of effect of helical wire-wrap parameters on the thermal hydraulic performance of 217 fuel pin bundle. (March 2015) - Gajapathy, R.; Velusamy, K.; Selvaraj, P.; Chellapandi, P.
Highlights: The effect of helical wire wrap parameters on the flow and temperature distributions of sodium in heat generating 217 pin fuel bundle have been predicted. The statistically averaged 3-dimensional conservation equations of mass, momentum and energy are solved along with k–ε turbulence model by varying the helical pitch and diameter of the spacer wire using customized Computational Fluid Dynamics (CFD) code CFDEXPERT. The transverse velocity, friction factor and Nusselt number are found to be inversely proportional to the helical pitch and directly proportional to the helical wire diameter. Based on the parametric study, useful correlations have been proposed for Nusselt number as a function of Reynolds number, helical pitch and P/D, for use in core thermal hydraulics. The circumferential clad sodium temperature distribution for various helical pitch and wire diameters are presented. Abstract: In fast reactors, the fuel pins are wound with helical wire-wrap spacer to provide support for the fuel pins and to provide space for sodium coolant to flow through the bundle. Due to the helical wire-wrap spacer, the coolant not only flows in axial direction but also in a transverse direction. This transverse flow provides better mixing of coolant among the sub channels and due to this, the heat transfer coefficient of the coolant increases. But, the frictional resistance to flow also increases. The effect of helical wire wrap parameters on the flow and temperature distributions of sodium in heat generating 217 pin fuel bundle and the variation of friction factor and Nusselt number as a function of helical wire parameters have been predicted. Toward this, the statistically averaged 3-dimensional conservation equations of mass, momentum and energy are solved along with k–ε turbulence model by varying the helical pitch and diameter of the spacer wire using customized Computational Fluid Dynamics (CFD) code CFDEXPERT. The geometric details of the fuel pin bundle and heat flux are similar to that of the Indian Prototype Fast Breeder Reactor (PFBR) that is currently in an advanced stage of construction. Based on detailed parametric study, it is found that the transverse flow induced by wire-wrap increases if the helical pitch is reduced. As a consequence of this, the friction factor and the Nusselt number increase with reduction in helical pitch. When the wire diameter is reduced, the pin bundle becomes tighter with high resistance for transverse flow. As a result of the reduced cross flow, the friction factor as well as Nusselt number decrease when wire diameter is reduced. Based on the computational data, suitable correlations have been derived for estimation of Nusselt number in 217 pin fuel bundle for a range of practical interest in fast reactor core design. It is also seen that the clad temperature decreases with decrease in helical pitch and increase in wire diameter due to increase in the transverse flow and associated enhancement in heat transfer coefficient. It is seen that the sodium temperature difference between the central sub-channels in the various rows of pin bundle and the peripheral sub-channels at the same hexagonal face is lower for shorter helical pitch and larger helical wire diameter which is attributed to the enhanced heat exchange due to higher cross flow in these cases.